Walking in European cities: A gender perception perspective - Pirra, M.; Kalakou, S.; Lynce, A. R.; Carboni, A. (Transportation Research Procedia, 2023)
The COVID-19 pandemic has brought many changes in daily mobility, such as a general increase in the use of active means. However, the shift towards a different mode of transport is always influenced by various aspects that can affect users in distinct ways. Gender is among those factors, and research on this aspect has started to spread in the last decade. In this context, this work investigates how gender could impact the perception of pedestrians in Europe. A survey was designed and spread in Winter 2020- Summer 2021, collecting more than 4000 responses in 10 European regions/countries analysed - France, Italy, Spain, Greece, Portugal, Baltic States, German, Scandinavia, Romania and the United Kingdom. General statistics on the mode chosen for the most frequent journey on a weekday show different trends, with a more significant number of female walkers than males. Gender equity while escorting dependents is found in more than half of the samples, especially in northern European countries. Further analyses are based on the respondents' replies to satisfaction statements regarding walking conditions. Comparing the results from the 10 samples, the satisfaction levels of pedestrians for most samples are lower for women, except for the Romanian sample, where men are less satisfied. Results indicate a difference in the perception of security between men and women in most samples. From the pedestrians' group, women feel more insecure and less satisfied with the provided infrastructure while walking on the streets than men; thus, the proposal of adequate ameliorations is essential to push people to choose this sustainable and equitable active mode for their daily mobility.